Respuesta :

Answer:

see explanation

Step-by-step explanation:

Given that x = - [tex]\frac{4}{3}[/tex] is a solution of the equation, then

Substitute this value into the equation and solve for b

21 (- [tex]\frac{4}{3}[/tex] )² + b (- [tex]\frac{4}{3}[/tex] ) - 4 = 0

21 × [tex]\frac{16}{9}[/tex] - [tex]\frac{4}{3}[/tex] b - 4 = 0

[tex]\frac{112}{3}[/tex] - [tex]\frac{4}{3}[/tex] b - 4 = 0

Multiply through by 3

112 - 4b - 12 = 0

100 - 4b = 0 ( subtract 100 from both sides )

- 4b = - 100 ( divide both sides by - 4 )

b = 25 ← value of b

The equation can now be written as

21x² + 25x - 4 = 0 ← in standard form

with a = 21, b = 25, c = - 4

Use the quadratic formula to solve for x

x = ( - 25 ± [tex]\sqrt{25^2-(4(21)(-4)}[/tex] ) / 42

  = ( - 25 ± [tex]\sqrt{961}[/tex] ) / 42

  = ( - 25 ± 31 ) / 42

x = [tex]\frac{-25-31}{42}[/tex] = [tex]\frac{-56}{42}[/tex] = - [tex]\frac{4}{3}[/tex]

or x = [tex]\frac{-25+31}{42}[/tex] =  [tex]\frac{6}{42}[/tex] = [tex]\frac{1}{7}[/tex]

The other solution is x = [tex]\frac{1}{7}[/tex]

ACCESS MORE